1999
DOI: 10.1038/sj.bjp.0702303
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoconstrictor effect of thrombin and thrombin receptor activating peptide in guinea‐pigs in vivo

Abstract: 1 Several thrombin cellular e ects are dependent upon stimulation of proteinase activated receptor-1 (PAR-1) localized over the cellular surface. Following activation by thrombin, a new Nterminus peptide is unmasked on PAR-1 receptor, which functions as a tethered ligand for the receptor itself. Synthetic peptides called thrombin receptor activating peptides (TRAPs), corresponding to the N-terminus residue unmasked, reproduce several thrombin cellular e ects, but are devoid of catalytic activity. We have evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…72 These reports suggest a functional relationship of PAF in the pathophysiology of asthma. The potential role of platelets in lung function disorders accompanying asthma is further supported by findings that bronchoconstriction induced by either intratracheal instillation of lipopolysaccharide 73 or intravenous injection of thrombin 74 required the presence of functionally intact platelets in the circulation. In accordance, platelet depletion resulted in a significant inhibition of allergen-induced airway hyper-responsiveness to inhaled histamine in rabbits, 75 and P-selectin-deficient mice demonstrated lower levels of airway hyper-responsiveness than wild-type mice 61 with cockroach allergen-induced lung inflammation.…”
Section: Platelets and Asthmamentioning
confidence: 60%
“…72 These reports suggest a functional relationship of PAF in the pathophysiology of asthma. The potential role of platelets in lung function disorders accompanying asthma is further supported by findings that bronchoconstriction induced by either intratracheal instillation of lipopolysaccharide 73 or intravenous injection of thrombin 74 required the presence of functionally intact platelets in the circulation. In accordance, platelet depletion resulted in a significant inhibition of allergen-induced airway hyper-responsiveness to inhaled histamine in rabbits, 75 and P-selectin-deficient mice demonstrated lower levels of airway hyper-responsiveness than wild-type mice 61 with cockroach allergen-induced lung inflammation.…”
Section: Platelets and Asthmamentioning
confidence: 60%
“…In platelet-depleted animals, pulmonary pressure increased by only 17% of the value recorded for animals with normal platelet numbers. Cicala et al [39] showed that substantial bronchoconstriction in the guinea-pig airways can also be achieved by intravenous thrombin administration. However, they observed that reduction in lung function in this model is averted in animals previously treated with anti platelet serum (APS), suggesting that platelets are essential for a bronchoconstrictive reaction.…”
Section: Experimental Evidence For a Role Of Platelets In Asthmamentioning
confidence: 97%
“…Although PAR-1 expression had never been described in the lung, PAR-1 mRNA had previously been detected in cultured alveolar macrophages. 48 Furthermore, specific agonists of this receptor have been shown to cause bronchoconstrictor responses in experimental animals, 49 suggesting that the lung does indeed express functional PAR-1 receptors. Our studies showed that PAR-1 was expressed on the bronchial epithelium in the lungs of all experimental animals, with no evidence of altered expression after bleomycin instillation.…”
Section: Active Thrombin and Par-1 Are Increased In Bleomycin-inducedmentioning
confidence: 99%